Epigenetic marks of prenatal air pollution exposure found in multiple tissues relevant for child health. (May 2019) - Ladd-Acosta, Christine; Feinberg, Jason I.; Brown, Shannon C.; Lurmann, Frederick W.; Croen, Lisa A.; Hertz-Picciotto, Irva; Newschaffer, Craig J.; Feinberg, Andrew P.; Fallin, M. Daniele; Volk, Heather E.
Abstract: Background: Prenatal air pollution exposure has been linked to many adverse health conditions in the offspring. However, little is known about the mechanisms underlying these associations. Epigenetics may be one plausible biologic link. Here, we sought to identify site-specific and global DNA methylation (DNAm) changes, in developmentally relevant tissues, associated with prenatal exposure to nitrogen dioxide (NO2 ) and ozone (O3 ). Additionally, we assessed whether sex-specific changes in methylation exist and whether DNAm changes are consistently observed across tissues. Methods: Genome-scale DNAm measurements were obtained using the Infinium HumanMethylation450k platform for 133 placenta and 175 cord blood specimens from Early Autism Risk Longitudinal Investigation (EARLI) neonates. Ambient NO2 and O3 exposure levels were based on prenatal address locations of EARLI mothers and the Environmental Protection Agency's AirNOW monitoring network using inverse distance weighting. We computed sample-level aggregate methylation measures for each of 5 types of genomic regions including genome-wide, open sea, shelf, shore, and island regions. Linear regression was performed for each genomic region; per-sample aggregate methylation measures were modeled as a function of quantitative exposure level with covariate adjustment. In addition, bumphunting was performed to identify differentially methylated regions (DMRs) associated with prenatal O3 and NO2 exposures in each tissue and by sex, with adjustment for technical and biological sources of variation. Results: We identified global and locus-specific changes in DNA methylation related to prenatal exposure to NO2 and O3 in 2 developmentally relevant tissues. Neonates with increased prenatal O3 exposure had lower aggregate levels of DNAm at CpGs located in open sea and shelf regions of the genome. We identified 6 DMRs associated with prenatal NO2 exposure, including 3 sex-specific. An additional 3 sex-specific DMRs were associated with prenatal O3 exposure levels. DMRs initially detected in cord blood samples (n = 4) showed consistent exposure-related changes in DNAm in placenta. However, the DMRs initially detected in placenta (n = 5) did not show DNAm differences in cord blood and, thus, they appear to be tissue-specific. Conclusions: We observed global, locus, and sex-specific methylation changes associated with prenatal NO2 and O3 exposures. Our findings support DNAm is a biologic target of prenatal air pollutant exposures and highlight epigenetic involvement in sex-specific differential susceptibility to environmental exposure effects in 2 developmentally relevant tissues. Highlights: Prenatal air pollutant exposure is associated with neonate DNA methylation changes. Increased prenatal ozone exposure associates with global losses of methylation. Locus-specific air pollutant methylation changes occur in placenta and cord blood. Some locus-specific methylation changes are sex-specific.